No longer left behind: The impact of return migrant parents on children's performance - Zhiqiang Liu; Li Yu; Xiang Zheng (Asian Development Bank Institute (ADBI), 2017)
Using data from a rural household survey for the People's Republic of China in 2009, we examine the impact of parental migration on children's educational outcomes. Consistent with the findings of a large empirical literature, we find that parental migration has a significantly negative impact on left-behind children's educational outcomes as measured by test scores in Chinese and mathematics. However, unlike many of the existing studies on the subject, we focus on the remediation effect of return migrant parents on once-left-behind children's performance. This empirical strategy allows us to avoid the endogeneity issue concerning the migration decision that may have contaminated previous studies. We find evidence that return migrant parents help alleviate the harm caused by parental migration. We explore two channels through which return migrant parents may improve children's school performance. One is that children spend more time studying following migrant parents' return. The other is that return migrant parents spend more on their children's education. We also find evidence suggesting that the remediation effect is stronger for children attending primary school and for daughters.
Keywords: J24; O12; O15; 330; migration; left-behind children; educational outcomes; People's Republic of China